Elimination behavior in the female domestic cat: Burying and smelling - Implications for chemical communication - Ferreira, Giovanne Ambrosio; Meneguello, L.ígia [UNESP]; Genaro, Gelson (Elsevier, 2024)
Olfactory communication is an important means of chemocommunication among animals, particularly in relation to reproduction. This study investigated the elimination behavior patterns of defecation and urination in female cats (Felis catus) from different age and reproductive status groups, including kittens, young adults, non-receptive adults, and nursing adults. Special attention was given to the number of movements (using the forelimbs) made during excreta concealment and the time (in seconds) spent on this process. Comparisons were conducted separately for feces and urine between the age groups. Significant differences (P <0.05) were observed in urine processing among non-receptive and nursing females, as well as kittens. Non-receptive females consistently made fewer movements to cover their urine, and less time was dedicated to this process. Comparisons between feces and urine within the same age group also revealed significant behavioral differences (P <0.05). Feces required a greater number of movements and more time compared to urine. These findings emphasize how different phases of a cat's life cycle influence the behavior of burying excretions (feces and urine), underscoring the importance of these excreta in olfactory communication.
Keywords: Domestic female cat; Excretion pattern; Feces; Urine